Study on the effect of Variations in Earth-Surface Gravity Depending on the Shape and Position of the Earth Radius and Age of the Universe Using General Relativity and Euclidean Geometry - Nagy, Tibor Endre (Challenging Issues on Environment and Earth Science Vol. 8, 2021)
In this work, we aimed to see how changes in the Earth's gravitational field in the context of general relativity modify the radius and age values of the universe in the previously developed distance-determining model. By applying the relationships of light propagating in accelerating systems and gravity to the Earth moving with the Milky Way galaxy in the expanding universe and to the light propagating in the surface gravity of our planet moving in this way, the radius and age of the universe can be determined. For a redshift extent of 3.1415 in the cosmos, we can determine a so-called “short evolving distance” from the Einstein equation. Knowledge of the entire plane angle (2.\(π\)) and the deviating angle of a light beam (\(α\)) passing through the Earth’s surface gravity it is possible to determine extreme distances by utilizing the rules of trigonometry. This “long evolving distance,” which is approximately in the range of the radius of the universe, can be transformed into the “evolving time” divided by the speed of light. Based upon this dating method, the universe may have been formed at an average value of 13.7536 billion years. In addition to the cosmos radius and age, different but small changes can be observed in these, taking into account the changes in the Earth's surface gravity associated with its shape and position. These values fall between 13.6879 and 13.8498 billion years, almost completely covering the range given by the analysis of the measurement results of the WMAP and Planck satellites.